Fluorescent labeling of s2T-incorporated DNA and m5s2U-modified RNA. (1st June 2021) - Yu, Ping; Zhou, Honglin; Li, Yuanyuan; Du, Zhifeng; Wang, Rui
Abstract: We report herein comprehensive investigations of alkylation/sulfur exchange reactions of sulfur-containing substrates including nucleosides such as s 2 U, m 5 s 2 U, s 4 U, s 2 A and s 2 T-incorporated DNA enable by comprehensive screenings of the reagents (2a–2h ). It has been proven that iodoacetamide (2a ) displays the most promising feasibility toward sulfur-containing substrates including s 2 T, s 2 U, m 5 s 2 U, s 4 U and s 2 A. In sharp contrast, the alkylation process with S-benzyl methanethiosulfonate (BMTS, 2h ) displays the best application potential only for s 4 U. Based on these results, the fluorescent labeling of s 2 T-incorporated DNA and m 5 s 2 U-modified RNA has been achieved. Supplemental data for this article is available online at https://doi.org/10.1080/15257770.2021.1942044 .